Equilíbrio de fases de progesterona em gases comprimidos - Favareto, Rogério (2006)
In this work, a pertinent study on the phase behavior of binary systems involving progesterone in compressed and/or supercritical fluids is presented. For the experimental data measurements of phase equilibrium to vapor-liquid (V-L) and solid-fluid (S-F) a variable volume cell, with a front sapphire window for visualization of phase transitions was used - a synthetic static method. For the systems CO2+chloroform and propane+chloroform were verified V-L phases transition type, for the first one bubble points (BP) as well as dew points (DP) were verified. And, for the second system, just bubble points were observed. For the systems CO2+progesterone, propane+progesterone and n-butane+progesteron, besides of the V-L (BP phase transition types) equilibrium, solid-fluid (S-F) transitions were also verified. The experimental data obtained were modeled using the Peng-Robinson equation cubic of state (EOS-PR), with the quadratic mixture rule of van der Waals, which was capable to correlate the experimental data in an efficient way. From the data obtained in the present work, it was verified that the progesterone presents lower solubility in CO2. However, the solubility of this steroid is more accentuated in n-butane and in propane, respectively, when compared with values of CO2.